2017
DOI: 10.1177/0306624x17703719
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Community-Oriented Policing Program in Taiwan

Abstract: This study was conducted to evaluate the effect of a community-oriented policing (COP) by documenting results for 16 quantitative outcome variables, including crime incidents, crime clearance, residents' subjective feelings regarding police performance and community safety, and job satisfaction among police officers. The statistical techniques used to analyze the data involved ARIMA interrupted time series, t tests, the Wilcoxon paired signed-rank test, and Pearson's correlation. The quantitative results obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…Neste contexto, "chamar os infratores para prestar contas" foi a terceira dimensão mais utilizada para avaliar o desempenho policial, com 16 Desempenho de organizações policiais: revisão sistemática da literatura | 280 Revista do Serviço Público (RSP), Brasília 72 (1) 262-291 jan/mar 2021 pesquisas. O número de policiais (Weisburd et al, 2010;Doerner;Doerner, 2012;Asif et al, 2018;Agarwal et al, 2019;Sinuany-Stern;Alper, 2019) e o tipo de crimes praticados (Weisburd et al, 2010;Doerner;Doerner, 2012;Hur, 2013;Demers;Rossmo, 2015;Kuo;Shih, 2018;Vidal;Kirchmaier, 2018;Scott et al, 2019) foram as variáveis mais empregadas para avaliar essa dimensão de desempenho. Na maioria das pesquisas foi constatado que o maior número de policiais implica mais crimes apurados.…”
Section: Dimensões De Desempenho Variáveis Mais Utilizadas E Principais Resultados De Pesquisaunclassified
See 1 more Smart Citation
“…Neste contexto, "chamar os infratores para prestar contas" foi a terceira dimensão mais utilizada para avaliar o desempenho policial, com 16 Desempenho de organizações policiais: revisão sistemática da literatura | 280 Revista do Serviço Público (RSP), Brasília 72 (1) 262-291 jan/mar 2021 pesquisas. O número de policiais (Weisburd et al, 2010;Doerner;Doerner, 2012;Asif et al, 2018;Agarwal et al, 2019;Sinuany-Stern;Alper, 2019) e o tipo de crimes praticados (Weisburd et al, 2010;Doerner;Doerner, 2012;Hur, 2013;Demers;Rossmo, 2015;Kuo;Shih, 2018;Vidal;Kirchmaier, 2018;Scott et al, 2019) foram as variáveis mais empregadas para avaliar essa dimensão de desempenho. Na maioria das pesquisas foi constatado que o maior número de policiais implica mais crimes apurados.…”
Section: Dimensões De Desempenho Variáveis Mais Utilizadas E Principais Resultados De Pesquisaunclassified
“…Em relação à origem dos dados, 35 pesquisas usaram dados primários, coletados pelos próprios pesquisadores, e 21 artigos utilizaram dados secundários, fornecidos por terceiros (governos, polícias, entre outros). Dos cinco artigos que usaram dados primários e secundários, três empregaram abordagens mistas (qualitativa e quantitativa) para efetuar a pesquisa (Lacey;Cuganesan;Goode;Jacobs, 2012;Rengifo;Fratello, 2015;Kuo;Shih, 2018).…”
Section: Características Metodológicas Dos Artigos Revisadosunclassified
“…The positive view can be explained by day-to-day collaboration with individuals from the general public rather than dealing with problematic individuals, as well as the community's trust and positive perception of the police (Skolnick & Bayley, 1988;Trojanowicz & Bucqueroux, 1998). Thus, complete and consistent implementation of community policing was associated with higher job satisfaction in police officers (Brody, DeMarco, & Lovrich, 2002;Kuo & Shih, 2018). Community policing encourages police officers to apply their skills and experiences creatively and perceive their role as more valuable (Pelfrey, 2004;Skolnick & Bayley, 1988).…”
Section: Community Policingmentioning
confidence: 99%
“…Studies show the important benefits of community policing for communities and the police (Roh & Oliver, 2005;Xu, Fielder, & Flaming, 2005). Police-community relations and public confidence have been improved through the implementation of community policing (Cordner, 2000;Kuo & Shih, 2018;Skogan, 2006). Several studies indicated that officers who are involved in community policing have a more positive perception of the community and residents.…”
Section: Community Policingmentioning
confidence: 99%
“…NPA officers wear identical uniforms, conduct street patrols, issue citations, investigate crimes, and respond to citizen complaints. Members of the agency are stationed in neighborhood-based branches (called pai-chu-suo ) and engage in community-oriented policing (Kuo & Shih, 2018; Sun & Chu, 2006). In the recent three decades of democratization in Taiwan, locally elected political leaders are legally authorized to appoint their police chiefs from a list of candidates recommended by the NPA, which exercises administrative jurisdiction over all police departments and evaluates the performance of police chiefs (Cao et al, 2014).…”
Section: National and Local Law Enforcement Agencies In Democratic Tamentioning
confidence: 99%